2016
DOI: 10.1002/2016jd025507
|View full text |Cite
|
Sign up to set email alerts
|

Compounding factors causing the unusual absence of tropical cyclones in the western North Pacific during August 2014

Abstract: The western North Pacific (WNP) is a region where tropical cyclones (TCs) occur most frequently. However, no TCs occurred in August, climatologically the month of most frequent TC genesis, in 2014. Such absence of TC activity in August was approximately 3σ below the climatological mean (5.1) and occurred for the first time during 1945–2014. This study investigates the large‐scale factors responsible for the absence. While July–August 2014 was a period of weak El Niño condition, rainfall in the eastern North Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…In turn, the downward motion of the east–west overturning circulation anomaly may have caused an anomalous anticyclone in the WNP. The effect of CPEN–SST on the east–west overturning circulation in the North Pacific was supported by the numerical experiments (Hong et al ., ). Briefly, the CPEN–SST‐associated anomalous anticyclone in the WNP (Figure d) may have enhanced the prevailing southwesterly wind in the South China Sea, thus leading to a rainfall surplus in northern Taiwan and southern China in IP2.…”
Section: Resultsmentioning
confidence: 97%
“…In turn, the downward motion of the east–west overturning circulation anomaly may have caused an anomalous anticyclone in the WNP. The effect of CPEN–SST on the east–west overturning circulation in the North Pacific was supported by the numerical experiments (Hong et al ., ). Briefly, the CPEN–SST‐associated anomalous anticyclone in the WNP (Figure d) may have enhanced the prevailing southwesterly wind in the South China Sea, thus leading to a rainfall surplus in northern Taiwan and southern China in IP2.…”
Section: Resultsmentioning
confidence: 97%
“…2a). This absence of TC activity in August was observed at the rst time since 1945 (Hong et al 2016).…”
Section: Introductionmentioning
confidence: 83%
“…Previous studies have indicated that the eastward propagating ISO plays an important role in the absence of TCs over the WNP in August 2014 by inducing anomalous easterlies, which led to decreased moisture and vorticity, and increased divergence (Yang et al 2015;Hong et al 2016;Bian et al 2018). The pronounced different TC genesis numbers between 1996 and 2014 suggested that the TC genesis over the WNP in August 1996 must be forced by other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the significant negative correlation zones steadily located in the tropical eastern Pacific (TEP) from June to August. It may denote that the impact of the TEP SSTs is more important to TCGF in August (Hong et al ., 2016a).…”
Section: Possible Remote Forcing Effect Of Nta Sstsmentioning
confidence: 99%